Efficacy of Thyroid Hormone Replacement Therapy in Nasopharyngeal Carcinoma Patients with Radiation-Induced Subclinical Hypothyroidism - Lian, Chen-Lu; Chen, Gui-Ping; Zhou, Rui; Yu, Yi-Feng; Zhou, Ping; Lin, Qin; Wu, San-Gang (Experimental and Clinical Endocrinology & Diabetes, 2024)
Aims Hypothyroidism is a common side effect of radiotherapy for nasopharyngeal carcinoma. However, the impact of thyroid hormone replacement therapy on patients with radiation-induced subclinical hypothyroidism has not been extensively explored. This study aimed to analyze the efficacy of thyroid hormone replacement therapy in nasopharyngeal carcinoma patients with subclinical hypothyroidism.Methods Patients diagnosed with nasopharyngeal carcinoma who developed subclinical hypothyroidism after definitive radiotherapy between September 2019 and December 2020 were selected for inclusion in this study. Prior to thyroid hormone replacement therapy and after maintaining euthyroidism for 6–12 months through thyroid hormone replacement therapy, assessments using the SF36 Brief Health Status Scale and the Hypothyroidism-related Symptom Questionnaire were conducted via trained questionnaires. Lipid profiles were assessed at baseline and after 6–12 months of thyroid hormone replacement therapy. Statistical analyses were performed using matched samples T-test or Mann-Whitney U test.Results The median follow-up period was 14.5 months. The median score of hypothyroid symptoms was 5.5 out of 19 points, with the most common symptoms being chills (65.0%), fatigue (50.0%), weight gain (45.0%), and limb numbness (40.0%). Thyroid hormone replacement therapy did not significantly improve the quality of life, hypothyroidism-related symptoms, or blood lipid profile in patients. However, there was an observed downward trend in serum cholesterol levels following treatment (P=0.052).Conclusion Thyroid hormone replacement therapy did not have a significant impact on alleviating hypothyroid symptoms, improving quality of life, or enhancing lipid profiles in patients with radiation-induced subclinical hypothyroidism. Nevertheless, a potential decrease in serum cholesterol levels was noted after thyroid hormone replacement therapy.
Keywords: nasopharyngeal carcinoma; thyroid hormone replacement; subclinical hypothyroidism; lipid profile; quality of life; hypothyroid symptoms